Mulheres na luta pela terra: visibilidade e construção do território no Assentamento Horto Bela Vista em Iperó/SP - Souza, Leticia Lauane de (Universidade Federal de São Carlos, 2026)
The struggle for land in Brazil constitutes a historical process marked by territorial disputes, inequalities, and the organization of social movements that seek the right to remain in rural areas. In this context, women have played a crucial role, although they are often made invisible. this dissertation aims to understand how women establish themselves as constituent agents of the territory in the struggle for land, focusing on the Horto Bela Vista Settlement, located in Iperó/SP. The research is based on the understanding that the struggle for land in Brazil is marked by intense land tenure inequalities and intersected by power relations in which gender plays a central role. The methodology articulates archival research, fieldwork, and interviews with women from the settlement. Anchored in the theoretical framework of Agrarian Geography and gender studies, the collected data highlights that, although historically marginalized, women play a fundamental role in the constitution and maintenance of conquered territories, acting politically from the initial encampments to the consolidation of the settlement. The analysis of oral narratives reveals that gender relations in the countryside are still permeated by patriarchal structures, which are nonetheless being challenged by women's everyday practices and resistance. Thus, this research contributes to the debate on territory and the role of women in the struggle for land, highlighting their centrality in this process.
Women in the struggle for land: visibility and the construction of territory in the Horto Bela Vista Settlement in Iperó, São Paulo
Keywords: Luta pela terra; Território; Assentamento rural; Camponesas; Land struggle; Women; Territory; Rural settlement; Peasant women; CIENCIAS HUMANAS::GEOGRAFIA; 5. Igualdade de Gênero